Valproic acid induces three novel cytotoxic secondary metabolites in Diaporthe sp., an endophytic fungus from Datura inoxia Mill. Issue 12 (1st July 2018) - Sharma, Vishal; Singamaneni, Venugopal; Sharma, Nisha; Kumar, Amit; Arora, Divya; Kushwaha, Manoj; Bhushan, Shashi; Jaglan, Sundeep; Gupta, Prasoon
Graphical abstract: Highlights: Diaporthe sp ., an endophytic fungus was cultured in presence of valproic acid. Microbial extract was explored for isolation of induced secondary metabolites. Three novel compounds, xylarolides A and B and diportharine A were identified. Xylarolides A and B were found active against MIA-Pa-Ca-2 and PC-3 cell lines. Xylarolide A displayed significant DPPH scavenging activity with EC50 of 10.3 µM. Abstract: Addition of the valproic acid (histone deacetylases inhibitor) to a culture of an endophytic fungus Diaporthe sp. harbored from Datura inoxia significantly altered its secondary metabolic profile and resulted in the isolation of three novel compounds, identified as xylarolide A (1 ), diportharine A (2 ) and xylarolide B (3 ) along with one known compound xylarolide (4 ). The structures of all the compounds (1 –4 ) were determined by detailed analysis of 1D and 2D NMR spectroscopic data. The relative configurations of compounds 1 –3 were determined with the help of NOESY data and comparison of optical rotations with similar compounds with established stereochemistry. All the isolated compounds were screened for antibacterial, antioxidant and cytotoxic activities. Xylarolide A (1 ) and xylarolide (4 ) displayed significant growth inhibition of MIAPaCa-2 with an IC50 of 20 and 32 µ M respectively and against PC-3 with an IC50 of 14 and 18 µ M respectively. Moreover, compound 1 displayed significant DPPH scavenging activity with EC50 of 10.3 µ M using ascorbic acid as a positive control.